2018
DOI: 10.1186/s12913-018-2990-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, barriers and opinions on multidisciplinary team meetings: a survey in Swedish cancer care

Abstract: BackgroundCase review and discussion at multidisciplinary team meetings (MDTMs) have evolved into standard practice in cancer care with the aim to provide evidence-based treatment recommendations. As a basis for work to optimize the MDTMs, we investigated participants’ views on the meeting function, including perceived benefits and barriers.MethodsIn a cross-sectional study design, 244 health professionals from south Sweden rated MDTM meeting structure and function, benefits from these meetings and barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 33 publications
5
114
0
9
Order By: Relevance
“…The research team developed a questionnaire based on an earlier study on health professionals' experiences from local and regional MDTMs. 15 Information about the study and a link to an online questionnaire was distributed to all participants (N=241) by e-mail. Two reminders were sent.…”
Section: Respondents and Data Collectionmentioning
confidence: 99%
“…The research team developed a questionnaire based on an earlier study on health professionals' experiences from local and regional MDTMs. 15 Information about the study and a link to an online questionnaire was distributed to all participants (N=241) by e-mail. Two reminders were sent.…”
Section: Respondents and Data Collectionmentioning
confidence: 99%
“…Representation of patients’ preferences is largely sought when clinical information cannot decisively inform treatment planning. In these scenarios, the notion of “encountered authority” may be a persuasive factor in decision‐making with the objective that a conclusive recommendation is more likely …”
Section: Principles That Inform Mdt Meetingsmentioning
confidence: 99%
“…As an example, one study identified a 10% higher trial recruitment rate for colorectal patients managed through an MDT compared to patients not managed through MDT . MDT members in some tumor streams may not perceive MDT meetings to be an apt avenue for identification of patients suitable for clinical trials and most believe it is the responsibility of lead clinicians to identify relevant clinical trials for their patients . However, physician awareness of clinical trials is ad hoc.…”
Section: Principles That Inform Mdt Meetingsmentioning
confidence: 99%
“…Barriers in guideline implementation include lack of awareness, agreement, self‐efficacy, and outcome expectancy; patient preferences, ability, and behavior; limited time and time pressure by MDs; and reduced resources . As far as adherence to nutrition guidelines is concerned, a holistic multidisciplinary team including a dietitian is important for better delivery of the nutrition information, increased adherence to CPGs, and precise treatment recommendations to improve quality of care and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lower quality of care, inaccurate treatment recommendations, and higher healthcare costs are attributed to CPG nonadherence. With nutrition being a crucial component of cirrhosis treatment, our study underlines the existing gaps in MNT CPGs and provides evidence for the improvement of future guidelines.…”
Section: Discussionmentioning
confidence: 99%